The effect of understanding accounting and the use of accounting information systems on the quality of financial reports - Eka Setiajatnika; Riska Rachma Dewi (ARKA INSTITUTE, 2022)
This study aims to empirically prove the influence of accounting understanding and the use of accounting information systems on the quality of financial reports. The data analysis technique used in this study is multiple linear regression analysis. The results of multiple regression analysis indicate that variations in the quality of financial statements can be explained by variations in the variable understanding of accounting and the use of accounting information systems. The results show that accounting comprehension and the use of accounting information systems positively affect the quality of financial reports. The results of this study mean that the better understanding of accounting and the use of accounting information systems, the better the quality of financial statements